SISTEM INFORMASI PENJUALAN ALAT TULIS KANTOR BERBASIS WEB PADA TOKO QIRAN SHOP KAB. SERANG MENGGUNAKAN FRAMEWORK CODEIGNITER - Ulum, Bahrul (LPPM Universitas Bina Bangsa, 2024)
The advancement of technology and digitalization has driven companies, including office supplies stores like Toko Qiran Shop, to adopt web-based information systems. However, many office supplies stores still face challenges in optimizing their sales systems, particularly in implementing efficient web-based sales information systems. The main obstacles include the use of manual methods such as written records and worksheets in the sales process. This impacts the likelihood of registration errors, inaccurate calculations, and delays in transactions. Furthermore, inconsistencies in office supplies stock and a lack of customer complaint handling also lead to customer dissatisfaction. To overcome these challenges, this study applies SWOT analysis. This method helps identify the strengths, weaknesses, opportunities, and threats affecting business performance, such as Toko Qiran Shop. SWOT analysis assists in formulating effective improvement strategies. The primary objective of the study is to design an efficient web-based sales information system. It is anticipated that this system will enhance operational efficiency, better manage inventory, process transactions swiftly, and provide improved customer service. In an era of intensifying competition, the implementation of web-based sales information systems becomes crucial for Toko Qiran Shop's success. With the right technology, the store can meet customer expectations, navigate market changes, and remain relevant in the everevolving industry.